Detection of Upper Gastrointestinal Disorders in Patients with Positive Fecal Immunochemical Test (FIT) and Normal Colonoscopy: A Cross-Sectional Study - Sahar Ravanshad; Atefeh Golhasani; Hassan Mehrad-Majd; Mohammadhossein Taherynejad; Ali Beheshti Namdar (Journal of Coloproctology, 2024)
Introduction Colorectal cancer (CRC) is the second most prevalent cancer in the world, and the fecal immunochemical test (FIT) can be mentioned among the CRC screening methods based on the detection of occult blood in the feces, which may indicate upper gastrointestinal (UGI) malignancies; therefore, patients with a positive FIT but normal colonoscopy may be considered for a UGI endoscopy.